FROM DEVELOPMENT TO DEPLOYMENT: FOR A COMPREHENSIVE APPROACH TO ETHICS OF AI AND LABOUR - Posada, Julian (AoIR Selected Papers of Internet Research, 2020)
In recent years, government and policy organizations, private companies, and research agencies have been discussing the potential disruption caused by the deployment of AI systems in working environments. This paper traces contemporary discourse on the relationship between artificial intelligence and labour and discusses how these principles must be comprehensive in their approach to labour and AI. First, the paper asserts that ethical frameworks in AI alone are not enough to guarantee the rights of workers since they lack enforcement mechanisms and the participation of worker organizations. Secondly, it argues that current discussions on AI and labour focus on the deployment of these technologies in the workplace but ignore the essential role of human labour in their development, particularly in the different cases of outsourced labour around the world. Finally, the paper recommends the use of already existing human rights frameworks on working conditions – notably the International Labour Organization conventions on the right of collective bargaining, the abolition of discrimination at work, and the right to equal remuneration – as a basis for a more comprehensive ethical framework on AI labour. It concludes by arguing that the central question regarding the future of work will not be whether intelligent machines will replace humans, but who will own and have a say on the systems that will ultimately work alongside humans.